PENERAPAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) DALAM PEMBUATAN APLIKASI MOBILE EDUKASI LINGKUNGAN â€œCINTA MANGROVEâ€ - Hermansyah Hermansyah; Rian Farta Wijaya; Sri Wahyuni; Agil Dwi Putra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: The degradation of mangrove ecosystems in coastal areas has become an increasingly concerning environmental issue, partly due to the lack of public knowledge and awareness regarding the importance of mangrove conservation. This study aims to develop a mobile environmental education application entitled â€œCinta Mangroveâ€ by applying the Multimedia Development Life Cycle (MDLC) method. The MDLC method consists of six stages: concept, design, material collection, assembly, testing, and distribution. In the evaluation stage, testing was conducted using pre-tests and post-tests to measure the improvement in usersâ€™ knowledge before and after using the application. Beta testing was carried out by comparing pre-test and post-test results through questionnaires. The results showed an increase in participantsâ€™ average understanding from 60% before using the application to 85% after its use. The findings indicate a significant improvement in participants' comprehension of the functions and importance of mangrove preservation. The "Cinta Mangrove" application is considered effective in delivering educational content in an engaging and user-friendly manner, and it successfully raises environmental awareness among the community. Therefore, this application can serve as an innovative solution to support educational and conservation efforts for mangrove ecosystems in coastal areas.Â Keywords: Agile, application development, ordering goods, delivery goods, information Â Â Â Â Â Â Â Â Â Â Â  Â Â Â  technology. Abstrak: Kerusakan ekosistem mangrove di kawasan pesisir merupakan permasalahan lingkungan yang semakin memprihatinkan, salah satunya disebabkan oleh kurangnya pengetahuan dan kepedulian masyarakat terhadap pentingnya pelestarian mangrove. Penelitian ini bertujuan untuk mengembangkan aplikasi mobile edukasi lingkungan bertajuk â€œCinta Mangroveâ€ dengan menerapkan metode pengembangan Multimedia Development Life Cycle (MDLC). Metode MDLC terdiri dari enam tahapan, yaitu konsep, desain, pengumpulan material, pembuatan, pengujian, dan distribusi. Pada tahap evaluasi, dilakukan pengujian melalui pre-test dan post-test untuk mengukur peningkatan pengetahuan pengguna sebelum dan sesudah menggunakan aplikasi. Evaluasi dilakukan melalui pengujian beta dengan membandingkan hasil pre-test dan post-test melalui kuisioner. Hasilnya menunjukkan adanya peningkatan rata-rata pemahaman peserta dari 60% sebelum menggunakan aplikasi menjadi 85% setelah penggunaan. Hasil pengujian menunjukkan peningkatan signifikan dalam pemahaman peserta terhadap fungsi dan pentingnya pelestarian mangrove. Aplikasi â€œCinta Mangroveâ€ dinilai efektif dalam menyampaikan materi edukatif secara menarik, mudah digunakan, serta mampu meningkatkan kesadaran lingkungan masyarakat. Dengan demikian, aplikasi ini dapat menjadi solusi inovatif dalam mendukung upaya edukasi dan konservasi mangrove di wilayah pesisir.Â Kata kunci: MDLC, Edukasi Lingkungan, Aplikasi Mobile, Mangrove, Pesisir